EVALUASI PROYEK REHABILITASI PEMBANGUNAN GEDUNG DI TINJAU BERDASARKAN WAKTU DAN BIAYA PENGERJAAN (Studi Kasus : Proyek Pembangunan MTsN Paron Kab. Ngawi) - Widhiarto, Herry; Nugroho, Meriana Wahyu (EXTRAPOLASI: Jurnal Teknik Sipil, 2014)
The development of construction project currently becomes a more complicated case. The implementation of construction project is a series of interdependent activity through project management system from plan stage up to the implementation itself. The project management system involves the workforce, cost, time, equipment and others , and also schedule delay which effects cost consumming that must be ignored. This study analysis how to determine optimal project time & cost. This case study is performed on the renovation of MTsN Paron Ngawi Regency building. The secondary data involves project cost estimate, time schedule, price analysis list of materials and wages which are analysed further by acceleration crashing methode and overtime extention. From the acceleration process , proved that optimal project time of MTsN Paron Ngawi Regency renovation project is done by expediting the time into 56 days, while the total amount of optimal project cost is Rp. 194,041,862.00. The most optimal option of the acceleration is the augment of overtime, 1 hour,Â  which generatesÂ  project efficiency 0.35 %.Key words : time-cost trade off, optimal project cost, project management, crashing